From safety commitment to safety behavior: The mediating role of safety awareness - Shanshan Lu; Weiwei Zhu; Li Zhang; Haris Ahmad (PLoS ONE, 2025)
To deeply analyze the mechanism of workplace safety climate on employee safety behavior, a conceptual model of employee safety behavior was constructed based on the theory of stimulus-organism-response (SOR). Structural equation modeling was used to test the model and hypotheses. The results show that safety communication and safety regulation have a significant positive impact on employees’ safety commitment and, consequently, on their safety compliance behavior. However, safety communication has no significant impact on employees’ safety awareness. Safety regulation can significantly improve employees’ safety awareness, which in turn enhances their compliance behavior. Employees’ safety compliance behavior directly affects their participation behavior and plays a completely mediating role in the influence of safety commitment and safety awareness on safety participation behavior.